Communication Is Key: Language Learning and Language Acquisition in Interspecies Communication - Lorensen, Sara (Leviathan: Interdisciplinary Journal in English, 2024)
The relationship between language and communication has engaged researchers for more than a century. Studies have compared human language with animal communication systems, discussing to what degree the complex features and mechanisms that constitute human language have parallels and precursors in animal communication systems. This article discusses the characteristic design features of human language and concludes that language is a uniquely human feature, even if some aspects can also be identified in animal communication systems. The discussion of experiments aiming towards teaching human language to animals leads to the observation that there is a difference between understanding a language and using it to communicate. Human language, however, is effective as a means in interspecies relations pertaining to human-animal communication.